Students’ Perceptions of Using ChatGPT in Learning English Vocabulary: A Narrative Inquiry - Nafahatul Miskiyah; Alfina Lu’luuzzahro; Hasna Azzahra; Lia Roudlotul Jannah; Lianfin Sadida Atsmara; Amanda Destiana Habibah; Dewi Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
ChatGPT is increasingly used as a tool for learning English vocabulary among Indonesian EFL university students. Employing a qualitative narrative approach, the study explores students’ perceptions and experiences in utilizing ChatGPT to support vocabulary learning. Data were collected through participants’ accounts of their learning experiences and analyzed using thematic narrative analysis by Riessman. The findings reveal that ChatGPT promotes faster and more practical vocabulary learning by providing instant definitions, synonyms, and explanations, which enhance students’ understanding and confidence. Furthermore, its accessibility supports self-directed learning and increases learner motivation. However, several challenges were identified, including concerns about information accuracy, excessive dependence on technology, and the potential reduction of critical thinking skills. The study concludes that ChatGPT can serve as an effective vocabulary learning tool when used critically and accompanied by active verification of information, suggesting the need for guided and responsible integration of AI tools in EFL learning contexts.